Problematizing Gen-Z Muslims’ Historical Literacy About the Pandemic and Its Impact on Muslim Worship Practices - Imam Ghazali Said; Nyong Eka Teguh Iman Santosa; Suhandoko Suhandoko (Universitas Islam Negeri Mataram, 2022)
This study scrutinized the historical literacy of Generation Z (Gen Z) Muslims about the pandemic and its impact on Muslim worship practices. The pandemic has raised not only questions about health but also worship. Employing a qualitative approach that combined textual and fieldwork research, this study seeks to explain the historical literacy of Gen Z Muslims about the pandemic. It also explores the ways in which they respond to the diversity in Muslim worship practices during the pandemic and the extent to which their involvement increases their Islamic historical literacy. The study was carried out in Surabaya, involving several data collection methods, such as interviews, focused group discussions, and surveys. The study reveals that the historical literacy of Gen Z Muslims fell short of expectations. Furthermore, with regards to the impact of the pandemic on the adjustment of worship practices among Muslims in their community, Gen Z Muslims are divided into three groups: affirmative, negative, and ignorant. This study also shows that Gen Z Muslims have yet to be connected intensely with community networks that allow them to participate in and improve their historical literacy.